Charge Transport in 2D DNA Tunnel Junction Diodes - Yoon,M; Min,S-W; Dugasani,SR; Lee,YU; Oh,MS; Anthopoulos,TD; Park,SH; Im,S (Small, 2017)
The low reactive oxygen species production capability and the shallow tissue penetration of excited light (UV) are still two barriers in photodynamic therapy (PDT). Here, Au cluster anchored black anatase TiO2−x nanotubes (abbreviated as Au25/B-TiO2−x NTs) are synthesized by gaseous reduction of anatase TiO2 NTs and subsequent deposition of noble metal. The Au25/B-TiO2−x NTs with thickness of about 2 nm exhibit excellent PDT performance. The reduction process increased the density of Ti3+ on the surface of TiO2, which effectively depresses the recombination of electron and hole. Furthermore, after modification of Au25 nanoclusters, the PDT efficiency is further enhanced owing to the changed electrical distribution in the composite, which forms a shallow potential well on the metal–TiO2 interface to further hamper the recombination of electron and hole. Especially, the reduction of anatase TiO2 can expend the light response range (UV) of TiO2 to the visible and even near infrared (NIR) light region with high tissue penetration depth. When excited by NIR light, the nanoplatform shows markedly improved therapeutic efficacy attributed to the photocatalytic synergistic effect, and promotes separation or restrained recombination of electron and hole, which is verified by experimental results in vitro and in vivo.